Prevention of oral and maxillofacial trauma secondary to orofacial dyskinesias associated with anti-N-methyl-d-aspartate receptor encephalitis: a case series - Jeffrey W. Chadwick; Patricia J. Brooks; Jeffrey M. Singh; David K. Lam (BMC, 2021)
Abstract Background Anti-N-methyl-d-aspartate receptor encephalitis (anti-NMDARE) is a multi-stage autoimmune-mediated disease associated with a multitude of neuropsychiatric and dysautonomic features. Orofacial dyskinesias are frequently associated with this condition and manifest as abnormal movements of the orofacial musculature. These involuntary movements may result in significant trauma to the oral and maxillofacial complex including the avulsion of the dentition and orofacial lacerations. Case presentation We describe the course of two female patients with anti-NMDARE in whom significant involuntary self-inflicted maxillofacial trauma was suffered despite the use of complex parenteral sedation regimens. The application of traditional maxillomandibular wiring techniques and pharmacologic strategies, including botulinum toxin, to immobilize the mandible were initially unsuccessful. These difficulties led to the fabrication and wire-based fixation of a patient-specific acrylic oral appliance that maintained the mandible in a depressed position and mitigated all lateral and protrusive movements. Discussion and conclusions These cases illustrate the first known successful use of an appliance-based therapy for managing orofacial dyskinesias in the anti-NMDARE patient population through an adaptation of traditional maxillomandibular fixation techniques. This approach eliminated further orofacial trauma and afforded physicians with safer means to manage and assess patients afflicted with this condition during their protracted intensive care unit admissions.